Motivations and outcomes of compatible living donor–recipient pairs in paired exchange. Issue 1 (12th September 2021) - Chipman, Valerie; Cooper, Matthew; Thomas, Alvin G.; Ronin, Matthew; Lee, Brian; Flechner, Stuart; Leeser, David; Segev, Dorry L.; Mandelbrot, Didier A.; Lunow‐Luke, Tyler; Syed, Shareef; Hil, Garet; et al.
Abstract : Increasing numbers of compatible pairs are choosing to enter paired exchange programs, but motivations, outcomes, and system‐level effects of participation are not well described. Using a linkage of the Scientific Registry of Transplant Recipients and National Kidney Registry, we compared outcomes of traditional (originally incompatible) recipients to originally compatible recipients using the Kaplan–Meier method. We identified 154 compatible pairs. Most pairs sought to improve HLA matching. Compared to the original donor, actual donors were younger (39 vs. 50 years, p  < .001), less often female (52% vs. 68%, p  < .01), higher BMI (27 vs. 25 kg/m², p  = .03), less frequently blood type O (36% vs. 80%, p  < .001), and had higher eGFR (99 vs. 94 ml/min/1.73 m², p  = .02), with a better LKDPI (median 7 vs. 22, p  < .001). We observed no differences in graft failure or mortality. Compatible pairs made 280 additional transplants possible, many in highly sensitized recipients with long wait times. Compatible pair recipients derived several benefits from paired exchange, including better donor quality. Living donor pairs should receive counseling regarding all options available, including kidney paired donation. As more compatible pairs choose to enter exchange programs, consideration should be given to optimizing compatible pair and hard‐to‐transplant recipient outcomes. Abstract : Analysis of compatible pairs in a large kidney exchange identify motivations and potential benefits for the recipients as well as for the exchange.